The Mechanical Properties and Corrosion Behavior of Double-Layered Nano Hydroxyapatite-Polymer Coating on Mg-Ca Alloy - Bakhsheshi-Rad, Hamid Reza (Springer New York LLC, 2015)
Nano-hydroxyapatite (HA)/poly(e-caprolactone) (PCL) coatings with thickness of about 45-55 µm were prepared on the surface of a Mg-Ca alloy by a combination of electrochemical deposition and dip-coating methods. The results indicate that incorporation of nano-HA as an inner layer affects the porosity of the PCL-coated layer as top layer and enhances the corrosion resistance of Mg-Ca alloys. The nano-HA/PCL-coated samples showed higher Rp (823.1 kO cm2) and lower icorr (5.85E-2 µA/cm2) compared with uncoated. Significant enhancement in the compressive strength was observed in the both nano-HA/PCL and PCL compared with uncoated samples after 10 days immersion in SBF.